2018
DOI: 10.1111/1475-6773.12849
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a New York City Supportive Housing Program on Housing Stability and Preventable Health Care among Homeless Families

Abstract: Supportive housing placement was associated with improved housing stability and reduced preventable health care visits among homeless families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…Housing instability in general has been shown to be negatively associated with access to health services, mental health, and quality of life . Predictably, interventions that have been targeted at reducing housing instability have been associated with improvements in health and reductions in emergency department services . Evictions, a specific and very acute form of housing instability, have substantial and far‐reaching consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Housing instability in general has been shown to be negatively associated with access to health services, mental health, and quality of life . Predictably, interventions that have been targeted at reducing housing instability have been associated with improvements in health and reductions in emergency department services . Evictions, a specific and very acute form of housing instability, have substantial and far‐reaching consequences.…”
Section: Introductionmentioning
confidence: 99%
“…12 Several subsequent publications have also shown benefits from housing-focused interventions. [23][24][25] In general, however, the evidence for health outcome improvements from interventions focused on social determinants is thin. A different systematic review of interventions related to social determinants that included sixty-seven articles published up to 2017 found that only 30 percent (twenty articles) reported health out-comes and 27 percent (eighteen) reported health care costs.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the larger context, clearly, it is illegal for pharmacies to offer to purchase ART from PLWH, and study findings highlight the important role that supportive, ethical pharmacies play in the lives of this population. Barriers such as poor-quality housing are addressable, and studies with similar populations have shown that providing quality housing can be effective [ 106 ] and cost-effective [ 107 – 109 ]. Last, the present study uncovers numerous ways that African American/Black and Latino PLWH in low-SES contexts successfully manage a range of serious challenges and thus demonstrate substantial resilience.…”
Section: Discussionmentioning
confidence: 99%